Proceedings Particle Accelerator Conference
DOI: 10.1109/pac.1995.504710
|View full text |Cite
|
Sign up to set email alerts
|

Design of the PEP-II Low-Energy Ring

Abstract: The PEP-II Project, a collaboration of SLAC, LBL, and LLNL, began construction in January 1994. Since the Conceptual Design Report (CDR) [1] was issued in June 1993, considerable progress has been made at refining and optimizing the Low-Energy Ring. Lattice design has progressed considerably, with solutions obtained for the chromatic correction of the IR and new, more relaxed, parameters for the required wigglers. Based on the latter change, the number of RF stations was reduced from 5 to 4. A new concept for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…3 and the comparison made in Table III, it can be concluded that in order to achieve the design IP spot size for both ATF2 lattices a better field quality QF1FF should be used, as considered in [28]. To this end, in November of 2012 the QF1FF magnet was replaced by a 4Q17 type quadrupole [29] recycled from the PEPII LER accelerator [30]. The 4Q17 magnet has a better field quality with respect to the previous QF1FF as shown in Table IV.…”
Section: A Final Doublet Replacementmentioning
confidence: 99%
“…3 and the comparison made in Table III, it can be concluded that in order to achieve the design IP spot size for both ATF2 lattices a better field quality QF1FF should be used, as considered in [28]. To this end, in November of 2012 the QF1FF magnet was replaced by a 4Q17 type quadrupole [29] recycled from the PEPII LER accelerator [30]. The 4Q17 magnet has a better field quality with respect to the previous QF1FF as shown in Table IV.…”
Section: A Final Doublet Replacementmentioning
confidence: 99%